Atlas of laparoscopic gastrectomy for gastric cancer : high resolution image for new surgical technique /: high resolution image for new surgical technique. ([2019]) - (Surgeon), Huang, Chang-Ming; Zheng, Chao-Hui; Li, Ping; Xie, Jian-Wei
No abstract available